DESCRIPTION OF KNOWLEDGE OF WOMEN STUDENTS ABOUT MENSTRUATIVE INTERFERENCE (POLIMENOREA) - nur azizah; Suci Arsita Sari; wiwik muhidayati; agus ari afandi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
Menstrual cycle is abnormal can trigger polymenorhoe, polymenorhoe is shorter than 21thrid day of menstrual cycle. The number of bleeding day less than or same many of normal period. the research to know the discribe of knowledge about polymenorhoe on women student at high school health rejekwesi bojonegoro. Method is descriptif reaserch with simple random sampling, amount 46 responden. This research result indicates that less than some respondent is as much as 21 responden (45,7%) has knowledge is less about polymenorhoe. Conclusion is less than some responden had knowledge is less about polymenorhoe. To increase knowledge reproductive health by read materials, book form Lecture, internet acces and book.